2002
DOI: 10.2460/ajvr.2002.63.1061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of general anesthesia and minor surgical trauma on urine and serum measurements in horses

Abstract: Transient hyperglycemia and an increase in rine production accompanies a commonly used anesthetic technique for horses. The increase in urine flow is not trivial and should be considered in anesthetic management decisions. With the exception of serum glucose concentration and urine production, the effect of general anesthesia on indices of renal function in clinically normal horses is likely of little consequence in most horses admitted for elective surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…An increase in serum phosphate after induction of anaesthesia as seen in both groups in the present study has been reported earlier [ 47 - 49 ]. Johnson et al [ 47 ] and Lindsay et al [ 48 ] speculated that this phosphate derived from dephosphorylation of CP and ATP, since these were the most likely sources of phosphate.…”
Section: Discussionsupporting
confidence: 91%
“…An increase in serum phosphate after induction of anaesthesia as seen in both groups in the present study has been reported earlier [ 47 - 49 ]. Johnson et al [ 47 ] and Lindsay et al [ 48 ] speculated that this phosphate derived from dephosphorylation of CP and ATP, since these were the most likely sources of phosphate.…”
Section: Discussionsupporting
confidence: 91%
“…Increasing dietary protein and potassium will also increase urine volume; feeding a legume diet can result in a 3–4 times increase in urine flow over diets of Timothy hay or wheat straw . Experimentally baseline flow rates are reported in the range of 0.92–1.24 mL/kg/h, but most of these animals had been maintained on high protein, high potassium legume diets . Tasker () reported a flow rate of 0.52 mL/kg/h in horses on a mixture of Timothy and alfalfa hay .…”
Section: Discussionmentioning
confidence: 99%
“…16 Also, the increase in urine flow must be considered when making decisions regarding anesthetic management. 17 To our knowledge, there are no published reports on the diuretic effects of medetomidine and xylazine in cats. Given the differences among species, it is important to examine diuretic effects of both drugs in cats.…”
mentioning
confidence: 98%